Validity Evidence of the TRIACOG-Online Administered In-Person to Adults Post Stroke - Luana Comito Muner; Guilherme Domingos Martins; Ana Beatriz Santos Honda; Natália Becker; Jaqueline de Carvalho Rodrigues (Brain Sciences)
Background/Objectives: Neuropsychological assessment tools adapted for digital formats are crucial to expanding access and improving cognitive evaluation in post-stroke patients. This study aimed to examine the reliability, convergent validity, and criterion-related validity (concurrent and known-groups) of TRIACOG-Online, a computerized cognitive screening tool designed to assess multiple domains in post-stroke adults in person or remotely. Methods: 98 participants (47 neurologically healthy adults and 51 post-stroke patients) completed a sociodemographic questionnaire, the Mini-Mental State Examination—MMSE, G-38—Nonverbal Intelligence Test, and the TRIACOG-Online assessment. Evaluations were conducted in person, computer mediated. Results: TRIACOG-Online demonstrated high internal consistency (Cronbach’s α = 0.872; McDonald’s ω = 0.923). Statistically significant differences were found between groups in episodic memory, attention, executive functions, and numerical processing, with healthy individuals outperforming post-stroke participants. Effect sizes were medium to large in several domains, especially for visual memory. Validity evidence based on the relationship with external variables was supported by negative correlations with age and positive correlations with education and reading and writing habits, particularly in the clinical group. Educational level showed stronger associations with verbal memory and language, suggesting a protective role in post-stroke cognitive performance. TRIACOG-Online scores demonstrated evidence of convergent validity with MMSE and G-38. Conclusions: TRIACOG-Online shows strong psychometric properties for the cognitive assessment of post-stroke adults. Its computerized format represents a promising tool for clinical and research use in neuropsychology, especially for bedside applications.